2018
DOI: 10.1111/and.12983
|View full text |Cite
|
Sign up to set email alerts
|

Sperm retrieval by microdissection testicular sperm extraction and intracytoplasmic sperm injection outcomes in nonobstructive azoospermic patients with Klinefelter syndrome

Abstract: Klinefelter syndrome is the most frequent chromosomal abnormality in patients with nonobstructive azoospermia. The development of advanced assisted reproductive techniques, such as testicular sperm extraction and intracytoplasmic sperm injection, has provided the possibility of biological fathering in nonobstructive azoospermic patients with Klinefelter syndrome. We aimed to evaluate our sperm retrieval rate by microdissection testicular sperm extraction and to analyse the intracytoplasmic sperm injection outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
4
20
0
5
Order By: Relevance
“…Madgar et al, 36 for example, showed that testicular volume was significantly higher in men with positive SRR. However, there are several studies reporting that testicular atrophy does not affect the success of SR. 9,[27][28][29]32,37 Garolla et al, 28 indeed, observed a 23% SRR even in KS patients with testicles < 1 mL. Our results support these findings as we failed to find any relationship between testicular volume and SRR in NOA patients with KS.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Madgar et al, 36 for example, showed that testicular volume was significantly higher in men with positive SRR. However, there are several studies reporting that testicular atrophy does not affect the success of SR. 9,[27][28][29]32,37 Garolla et al, 28 indeed, observed a 23% SRR even in KS patients with testicles < 1 mL. Our results support these findings as we failed to find any relationship between testicular volume and SRR in NOA patients with KS.…”
Section: Discussionsupporting
confidence: 86%
“…30,31 Ozer at al. 32 34 We also confirm that SRR was not influenced by patient's age in a real-life study with a large cohort of Klinefelter men. According to this view, it has been postulated that the progressive hyalinization and fibrosis of seminiferous tubules that is accelerated with the onset of puberty in KS are not ubiquitous and it is possible to observe tubules with normal residual activity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Ozer et al 37 analyzed data from 110 KS men submitted to mTESE and found that lower FSH and higher tT values were predictors for positive SR. In particular, they showed that men with tT values ≥ 2.95 ng/ml had a 4‐time higher change of positive SR compared to those with tT levels below the threshold 37 . The combination of higher tT and lower LH values was also found to be associated with positive SR in adolescent and adult KS 12,38,39 .…”
Section: Discussionmentioning
confidence: 99%